AIP gene germline variants in adult Polish patients with apparently sporadic pituitary macroadenomas - Trofimiuk-Müldner, Małgorzata; Domagała, Bartosz; Sokołowski, Grzegorz; Skalniak, Anna; Hubalewska-Dydejczyk, Alicja (Frontiers in Endocrinology, 2023)
Introduction. Up to 5% of all pituitary tumors are hereditary e.g. due to MEN1 or aryl hydrocarbon receptor-interacting protein (AIP) genes mutations. Objectives. The study was aimed at the assessment of the frequency and characteristics of AIP-mutation related tumors in patients with apparently sporadic pituitary macroadenomas in the Polish population. Material and methods. The study included 131 patients (57 males, 74 females; median age 42 years) diagnosed with pituitary macroadenomas, and with a negative family history of familial isolated pituitary adenoma (FIPA) or multiple endocrine neoplasia type 1 (MEN1) syndromes. Sanger sequencing was used for the assessment of AIP gene variants. The study was approved by the Ethics Board of JUMC. Results. AIP variants were identified in five of the 131 included subjects (3.8%): one diagnosed with Cushing’s disease, two with acromegaly, and two with non-secreting adenomas. Patients harboring hereditary AIP gene alterations did not differ from the rest of the study group in median age at diagnosis (41.0 vs. 42.5 years, P=0.8), median largest tumor diameter (25 vs. 24 mm, P=0.6), gender distribution (60.0% vs. 56.3% females, P=0.8), secreting tumor frequency (60.0% vs. 67.5%, P=0.7), or acromegaly diagnosis frequency (40.0% vs.37.3%, P=0.9). Conclusions. In our series of apparently sporadic pituitary macroadenomas, AIP gene variants carriers did not differ substantially from patients with negative genetic testing. A risk factor-centred approach to AIP genetic screening may result in missing germline variants. Considering the clinical impact of such genetic variants and their relatively low penetrance, it is, however, doubtful if general genetic screening benefits the whole cohort of pituitary macroadenoma patients and their families.